Proposta de um sistema de bicicletas compartilhadas para uma cidade de médio porte - Olmos, Camilo Andrés Mora (Universidade Federal de São Carlos, 2021)
The bicycle-shared systems (BSS) in the world have provided many benefits to cities such as improvements in traffic, health, and the environment. The biggest success factor for shared bikes is the location of the stations. This work presents a proposal for a bicycle shared system for a medium-sized city (Araraquara, S.P.), establishing the locations of the stations and evaluating the characteristics of the municipality. Factors such as locations with a high concentration of travel (generating poles for trips), elements of the bus system, current and designed infrastructure for bicycles, points of interest in the city, topographic characteristics, and profile of bicycle users are considered. The proposed methodology uses the modeling of a Geographic Information System (GIS), which allows the determination of certain characteristics based on analyzes specific to geography such as distances, densities, mappings. In parallel, the GIS connects with decision-making models, such as the Analytical Hierarchical Process (AHP) and the Optimization of Multiple Objectives by Radio Analysis (MOORA). Such methods contributed to the construction of maps indicating the areas of high and medium possibility to locate the stations of the system of shared bicycles, from which three alternatives were generated that evaluated characteristics such as number of bicycles, type of system (manual or automatic) and operating cost. Of these alternatives, the most suitable proposes a mixed system, with a lower cost and an average of trips suitable for an appropriate operation. From the development of the work, it was also possible to characterize the participation of elements such as bicycle infrastructure, temperature and slope within the implementation of the shared bicycle system. Finally, with the progress of the work, Araraquara presented itself as a city with an important potential to implement a system of shared bicycles.
Proposal for a bicycle shared system for a medium-sized city
Keywords: Sistemas de bicicletas compartilhadas; Mobilidade urbana; SIG; AHP; MOORA; Bicycle-shared systems; Urban mobility; ENGENHARIAS::ENGENHARIA CIVIL